Answer :
Answer:
We conclude that the line of equation containing the point (3, -3) with the slope m =3 will be:
- [tex]y=3x-12[/tex]
The graph of the line is also attached.
Step-by-step explanation:
Given
- The point (3,-3)
- The slope m = 3
Using the point-slope form of the line equation
[tex]y-y_1=m\left(x-x_1\right)[/tex]
where
- m is the slope of the line
- (x₁, y₁) is the point
substituting the values m = 3 and the point (x₁, y₁) = (3,-3)
[tex]y-y_1=m\left(x-x_1\right)[/tex]
[tex]y-\left(-3\right)=3\left(x-3\right)[/tex]
Apply rule: -(-a) = a
[tex]y+3=3\left(x-3\right)[/tex]
subtract 3 from both sides
[tex]y+3-3=3\left(x-3\right)-3[/tex]
simplify
[tex]y=3x-12[/tex]
Therefore, we conclude that the line of equation containing the point (3, -3) with the slope m =3 will be:
- [tex]y=3x-12[/tex]
The graph of the line is also attached.
